Recurrent Aneurysmal Bone Cyst of the Distal Fibula Treated with Denosumab and Curettage - Philip B. Fontenot; Jose Jesurajan; Marilyn Bui; Damon Reed; Odion Binitie (Case Reports in Oncological Medicine)
We report the case of a 13-year-old girl with multiple recurrences of an aneurysmal bone cyst of the distal fibula successfully treated with denosumab and curettage. Aneurysmal bone cysts are locally aggressive lesions with high rates of recurrence. The novel use of denosumab with curettage in a long bone showed a favorable outcome with no adverse events or signs of recurrence three years after treatment.